Effect of farmyard manure, fertilizers and lime on quality parameters, nutrient uptake and productivity of maize (Zea mays) inacidic condition of north-western Himalayas - SHARMA, ALISHA; MOHAPATRA, ANKITA; SHARMA, R P; SANKHYAN, N K; MEENA, HARI MOHAN (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during rainy (kharif) seasons of (June to October) 2020 and 2021 at Research Farm of Chaudhary Sarwan Kumar Krishi Vishvavidyalaya, Palampur, Himachal Pradesh to assess the effect of fertilizers, FYM (farmyard manure) and lime on maize (Zea mays L.) productivity and quality in acidic soil. The experiment was conducted in a randomized complete block design (RCBD), comprised of 11 treatments, viz. T1, Control; T2, 100% NPK; T3, 100% NPK + 5 t FYM/ha; T4, 100% NPK + 10 t FYM/ha; T5, 100% NPK + lime (full dose through broadcasting); T6, 100% NPK + lime (1/10th dose through furrow application); T7, 100% NPK + 5 t FYM/ha + lime (full dose through broadcasting); T8, 100% NPK + 10 t FYM/ha + lime (full dose through broadcasting); T9, 100% NPK + 5 t FYM/ha + lime (1/10th dose through furrow application); T10, 100% NPK + 10 t FYM/ha + lime (1/10th dose through furrow application); and T11, Natural farming [Ghanajeevamrita (cow dung, 100 kg; cow urine, 10 litre; jaggery, 100 g and gram flour, 100 g)], replicated thrice. After the harvest of maize, the data on grain and stover yield, nutrient uptake and grain quality parameters (crude protein, P, Ca, and Mg content) were recorded. The results revealed that the integrated application of 100% NPK, FYM and lime significantly improved the nutrient uptake over the rest of the treatments. The application of 100% NPK + 10 tonnes FYM/ha + lime incorporation at the rate 100% lime requirement (LR) increased the stover and grain yield by 161 and 179% over 100% NPK, respectively. The quality parameters like crude protein content (10.10%), P content (0.42%), Ca content (0.27%) and Mg content (0.14%) were also recorded higher with application of 100% NPK along with FYM (10 t/ha) and lime (100% LR). The results suggested the importance of sustainable soil fertility management, particularly the beneficial effects of integrating chemical fertilizer with lime and FYM in improving maize yield, nutrient uptake, and grain quality, compared to the sole use of chemical fertilizers in an acidic soil.